A Modified Flux Regulation Method to Minimize Switching Frequency and Improve DTC-Hysteresis-Based Induction Machines in Low-Speed Regions - Alsofyani, Ibrahim Mohd; Kim, Keon Young; Lee, Sze Sing; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2019)
Direct torque control (DTC) suffers from flux droop owing to the long zero-voltage vectors at low motor speeds. Previous studies were able to attain flux regulation by imposing the continuous switching of forward and reverse active-voltage vectors by causing torque overshoots in the torque hysteresis bands (THBs). This led to an excessive increase in the switching frequency and larger torque and current ripples, thus reducing the drive efficiency. In this paper, a modified flux regulation method is proposed for the classical DTC using a single THB when flux droop occurs in a low-rotor-speed range. The proposed method can protect the DTC from flux droops at low speeds by reducing the duration of zero-voltage vectors and minimizing the number of reverse-voltage vectors. In addition, the proposed strategy is efficient in reducing torque and current ripples while operating at low motor speeds. Furthermore, a significant reduction in the switching frequency is obtained. The effectiveness of the proposed strategy is confirmed by simulation and experimental results.
Keywords: Direct torque control; Flux regulation; Flux regulation method; Induction machines; Low speed; Minimizing the number of; Reverse voltages; Zero voltage vectors; Direct torque control (DTC); flux regulation; induction motor; low speed